Ideas and concepts of long run growth - STEINDL, J. (PSL Quarterly Review, 2013)
With the exception of Marx and Schumpeter, the subjects of “long run” and technical progress have lain dormant from the Classics to the end of World War II. Since then, curiosity has again been aroused on two fronts. The first is from former colonies in development and the second is from a renewed optimism in mature industrial countries. The present article deals with the theory and literature that came about with regards to the latter area. In particular, the author considers the work of Harrod and Kalecki. JEL: O41, O42, E12